The Effect of Work Discipline, Motivation and Compensation on Employee Performance at PT. Alfa Scorpii - Reny Vera; Widya Natalia; Kelvin Kelvin; Lia Valensia; Ina Namora Putri Siregar (Institute of Computer Science (IOCS), 2020)
The purpose of this research is to know the effect of work discipline, motivation and compensation on employee performance. The research location at PT. Alpha Scorpii. The population of this research is 130 employees. Simple random sampling is used to choose 98 employees. This type of research is quantitative with survey methods. Data collection using questionnaires. Before the questionnaire was distributed to the sample employees, a validity test and a reliability test were conducted. Data analysis techniques used multiple linear regression. The results showed that (1) work discipline had a positive and significant effect on employee performance, (2) motivation had a positive and significant effect on employee performance, (3) compensation had a positive and significant effect on employee performance, (4) work discipline, motivation.